A case study on the risk management of Islamic banks in Malaysia - Azlan Ali, Rashidah Kamarulzaman,; Juliza Mohamed, Zainal Azhar Zainal Azim, (Opción, 2019)
The aim of the study is to investigate the risk management of Islamic banks in Malaysia via quantitative comparative methods like by using the return on average assets (ROAA) and return on average equity (ROAE) analyses. As a result, the Maybank Islamic Berhad performance was exceptionally well during 2011 to 2016 except 2011. In conclusion, in comparison to Industry average figure Maybank performed better than overall Islamic banking industry in Malaysia. On the risk side, Maybank Islamic remains at lower risk during this period.